Predictors of successful discontinuation from renal replacement therapy during AKI: A meta‐analysis. Issue 2 (19th November 2020) - Wang, Liya; Li, Jiameng; Sun, Si; Du, Heyue; Chen, Pengfan; Xu, Yicong; Shen, Yuxin; Xin, Shuzi; Dan, Yuqing; Li, Hancong; Chen, Junda; Li, Zi; et al.
Abstract: The predictors of weaning time of renal replacement therapy (RRT) remain controversial for special patients suffering from acute kidney injury (AKI). The present work aims to perform a meta‐analysis to evaluate proper predictors of RRT weaning in AKI patients. We systematically searched EMBASE, PubMed, and Cochrane Central Register of Controlled trials for literatures between 1984 and June 2019. Studies evaluating predictors of weaning success of RRT in patients of AKI were included. Random‐effects model or fixed‐effects model meta‐analyses were performed to compute a standard mean difference (SMD). Newcastle–Ottawa Scale was employed to assess the risk of bias. We included 10 observational trials including 1453 patients. Twelve predictors including urine output, serum creatinine, serum urea, mean arterial pressure, central venous pressure, lactate, serum potassium, serum bicarbonate, pH value, SOFA score, urinary urea, and urinary creatinine were identified, showing urine output ( p  = 0.0000), serum creatinine ( p  = 0.008), serum potassium ( p  = 0.02), serum bicarbonate ( p  = 0.01), pH value ( p  = 0.03), urinary urea ( p  = 0.002), and urinary creatinine ( p  = 0.02) were significantly associated with weaning success. With the limited evidence, we speculate that urine output, serum creatinine, serum potassium, serum bicarbonate, pH value, urinary urea, and urinary creatinine might be associated with successful weaning.